2019
DOI: 10.1186/s12914-019-0197-3
|View full text |Cite
|
Sign up to set email alerts
|

Human rights’ interdependence and indivisibility: a glance over the human rights to water and sanitation

Abstract: Background In 1948 the Universal Declaration of Human Rights was drawn up. The content of this document was further reflected two treaties, the Covenant on Civil and Political Rights, and the Covenant on Economic, Social and Cultural Rights. To try to maintain the interrelationship between the rights contained in each document, the idea that all rights are interdependent and indivisible was stressed. Based on this vision, this study aimed to explore the extent to which the violation of the human r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
(16 reference statements)
0
14
0
8
Order By: Relevance
“…In other words, any inequalities above the minimum requirements to fulfilling the right to health are legally permitted. In addition, these underlying determinants of health tend to be considered individually and sequentially, and thus underestimate the interlinked and cumulative effects of the determinants [ 68 ]. While the right to health approach, as used this review, does address equity within the 10 indictors, a more thorough analysis of the concepts of fairness and equity of the health policy beyond the right to health is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, any inequalities above the minimum requirements to fulfilling the right to health are legally permitted. In addition, these underlying determinants of health tend to be considered individually and sequentially, and thus underestimate the interlinked and cumulative effects of the determinants [ 68 ]. While the right to health approach, as used this review, does address equity within the 10 indictors, a more thorough analysis of the concepts of fairness and equity of the health policy beyond the right to health is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Seen in this light, communities’ inability to obtain access to water translates into their loss of autonomy, identity and freedom. In this sense, allowing these social groups access to water would enable them to fully exercise their capabilities, including those essential for their survival, besides transforming social and power relations [ 5 , 6 , 9 , 13 , 27 , 36 – 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Article 5 of the Vienna Declaration, adopted at the World Conference of Human rights in 2003, states that human rights are indivisible, interdependent and interrelated. In an assessment of access to water for homeless populations, for instance, it was shown that lack of access to water impacted on the human rights to education, work and leisure [ 39 ]. A similar situation is observed for the group analyzed in the present research as non-enjoyment of the HRWS also obstructed the associated population’s rights to food, health and an adequate standard of living.…”
Section: Discussionmentioning
confidence: 99%
“…A População em Situação de Rua (PSR) é definida como um grupo populacional possuidor em comum a pobreza, vínculos familiares fragilizados e/ou rompidos, ausência de emprego assalariado e das proteções derivadas ou dependentes dessa forma de trabalho, não tendo uma moradia convencional regular e fazendo da rua sua fonte renda, sustento e residência, sejam de forma temporária ou permanente. 1,2 Estima-se que, no mundo, existem entre 900.000 mil a 1,6 bilhões de pessoas em situação de rua, 3,4 e no Brasil em torno de 101 mil, 5 ainda que os estudos no país mostrem divergências nesse quantitativo, 2,6 o que demonstra e reforça a invisibilidade social da PSR perante a sociedade. 5 A PSR enfrenta barreiras, tais como o preconceito, estigmas sociais, discriminação pelas suas escolhas na vida, condição social, comportamento de risco à saúde, pobreza, condição precária de higiene, dentre outras, para acessar os serviços de saúde que preferencialmente ocorre nas unidades de urgência e emergência, quando a sua necessidade ultrapassa os limites da dor ou possui interferência direta na sua sobrevivência, realização das atividades diárias e organização social na rua.…”
Section: Introductionunclassified
“…1,2 Estima-se que, no mundo, existem entre 900.000 mil a 1,6 bilhões de pessoas em situação de rua, 3,4 e no Brasil em torno de 101 mil, 5 ainda que os estudos no país mostrem divergências nesse quantitativo, 2,6 o que demonstra e reforça a invisibilidade social da PSR perante a sociedade. 5 A PSR enfrenta barreiras, tais como o preconceito, estigmas sociais, discriminação pelas suas escolhas na vida, condição social, comportamento de risco à saúde, pobreza, condição precária de higiene, dentre outras, para acessar os serviços de saúde que preferencialmente ocorre nas unidades de urgência e emergência, quando a sua necessidade ultrapassa os limites da dor ou possui interferência direta na sua sobrevivência, realização das atividades diárias e organização social na rua. 2,[7][8][9][10] Partindo do pressuposto que a saúde é um direito fundamental do ser humano, e que são inerentes a ela, as ações que destinam a garantir as pessoas e a coletividade social o bem-estar físico, mental e social.…”
Section: Introductionunclassified